Pengaruh Kelengkapan Produk, Harga Dan Lokasi Terhadap Keputusan Pembelian Pada Toko Pertanian UD Eka Tani Ngronggot Kabupaten Nganjuk - Bela Arumawati; Moch Saleh Udin; Taufik Akbar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
In the modern era, the economy is experiencing rapid development in the business sector. With this, many companies have sprung up operating in the sales sector. This in the business world results in very tight competition because every company basically wants to be successful in the business it runs. Agricultural shops are one of the businesses whose target is the agricultural sector, because the majority of people in the Nganjuk area work as farmers. Even though in the Nganjuk Regency area there are many competitors in the agricultural sector, every consumer has reasons for their purchasing decisions because price and location can also influence purchasing decisions. Maintaining consumers to continue shopping at this agricultural shop is a way to maintain the company's survival. In order for agricultural shops to be able to keep consumers shopping at agricultural shops, the company approaches consumers to find out consumer needs and desires. This research aims to find out the influence of product completeness, price and location on purchasing decisions at the UD Eka Tani Ngronggot Agricultural Shop, Nganjuk Regency. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, hypothesis testing. The population in this study was 183 people and the sample used was 126 respondents using the Slovin formula. The results of research at the UD Eka Tani Ngronggot Agricultural Shop, Nganjuk Regency show that product completeness, price and location have a significant influence on purchasing decisions. These results are proven by the calculated F value of 5,548 with a significance of 0.001. The significance value is smaller than 0.050 (0.001 > 0.050).